Ajaran Agama dalam Al-Qur'an Surat Lukman Ayat 12-19 - Faisol, Achmad (Penerbit Kyai Mojo, 2022)
The purpose of writing this article is to analyze the concept of religious education in the Qur'an, as well as views of religious education from the perspective of Tafsir Al-Misbah sura Lukman verses 12-19, and what methods are contained in religious education from the perspective of Tafsir Al-Mishbah surah Lukman verse 12-19. The results of the study show that in addition to the educational and learning process there is representative material with the values ​​of Islamic teachings, there is also a kind of affection element which is one of the factors in success in education and learning. Thus in general from the surah Luqman there are principles of Islamic education methods, namely: religious, biological, psychological, and social principles. Educators should have characteristics and traits that will unite in the totality of their personality. In this case the characteristics of Muslim educators are having rubbaniyah character and nature, being sincere, patient, honest, always providing knowledge, being able to use teaching methods, being able to manage classes and students, knowing the psychological lives of students, being responsive, and being fair. In conveying his lessons using the following ways: by touching his heart, not giving up easily, based on compassion, explaining with rational arguments, gentle, patient, firm, and diligent.